Vatalanib for metastatic gastrointestinal stromal tumour (GIST) resistant to imatinib: final results of a phase II study - Joensuu, H (Nature Publishing Group, 2011)
BACKGROUND: Vatalanib (PTK787/ZK 222584) inhibits a few tyrosine kinases including KIT, platelet-derived growth factor receptors (PDGFRs) and vascular endothelial growth factor receptors (VEGFRs). We report efficacy and safety results of vatalanib in advanced gastrointestinal stromal tumour (GIST) resistant to imatinib or both imatinib and sunitinib. PATIENTS AND METHODS: Forty-five patients whose metastatic GIST had progressed on imatinib were enrolled. Nineteen (42.2%) patients had received also prior sunitinib. Vatalanib 1250 mg was administered orally daily. RESULTS: Eighteen patients (40.0% 95% confidence interval (CI), 25.7–54.3%) had clinical benefit including 2 (4.4%) confirmed partial remissions (PR; duration, 9.6 and 39.4 months) and 16 (35.6%) stabilised diseases (SDs; median duration, 12.5 months; range, 6.0–35.6+ months). Twelve (46.2%) out of the 26 patients who had received prior imatinib only achieved either PR or SD compared with 6 (31.6%, all SDs) out of the 19 patients who had received prior imatinib and sunitinib (P=0.324). The median time to progression was 5.8 months (95% CI, 2.9–9.5 months) in the subset without prior sunitinib and 3.2 (95% CI, 2.1–6.0) months among those with prior imatinib and sunitinib (P=0.992). Vatalanib was generally well tolerated. CONCLUSION: Vatalanib is active despite its narrow kinome interaction spectrum in patients diagnosed with imatinib-resistant GIST or with imatinib and sunitinib-resistant GIST.